The Implementation of Whole Language Approach by Using Padlet Learning Media in Non-Fiction Writing Material - Mubarokah, Rossida Fatma Syahrulina; Huda, Miftakhul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the implementation of Whole Language Ap-proach by using Padlet learning media in non-fiction writing material. Methodology: This study uses a qualitative descriptive research type based on the learning process by implementing the Whole Language Approach using interactive media called Padlet. The data collection techniques used are observation to determine the application of the Whole Language Approach and the use of the Padlet application, interviews to determine student learning characteris-tics, and written tests to determine students' writing abilities. Results: The results of this study show the student learning process and the students' non-fiction writing abilities. The student involvement in this writing learning is quite active in using the Padlet application. Students can learn several lan-guage skills gradually through the stages of the Whole Language Approach. Applications/Originality/Value: The use of the Padlet application also encourages interest which can be seen from the results of student writing with a high average.